The Effectiveness of Cognitive-Analytic Therapy in Women Diagnosed with Breast Cancer and Post-Traumatic Stress Disorder - Aikaterini, Κoutrouki; Manolis, Mentis; Stephanos, Vassilopoulos (International Journal of Psychotherapy Practice and Research, 2026)
The present study examines the effectiveness of Cognitive-Analytic Therapy (CAT) in women diagnosed with breast cancer and Post-Traumatic Stress Disorder (PTSD) on reducing PTSD symptomatology and improving their mental health state (depression, self-esteem, post- traumatic growth, quality of life, therapeutic alliance). Additionally, the investigation includes the determination of the demographic, socio-economic and medical factors’ impact on mental health indicators in women with breast cancer and PTSD. The sample was 188 women with breast cancer and PTSD at the Chemotherapy Unit of ‘Agios Andreas’ General Hospital in Patras. The questionnaire data were analyzed using descriptive and inferential statistical analysis in order to determine any statistically significant correlations between the experimental and the control group and between psychological scales and the demographic and socio-economic factors. The findings confirm the effectiveness of CAT in women with breast cancer and PTSD in reducing PTSD and depressive symptoms, improving self-esteem and quality of life, achieving greater post-traumatic growth, and fostering a better therapeutic relationship with the therapist. The demographic, socio-economic and medical factors examined affected dissimilarly each psychological scale, as statistically significant associations were found with some scales but not with others.
Keywords: breast cancer; post-traumatic stress disorder; cognitive-analytic therapy